Microparticles from Patients with Multiple Organ Dysfunction Syndrome and Sepsis Support Coagulation through Multiple Mechanisms - Joop, Karin; Berckmans, René J.; Nieuwland, Rienk; Berkhout, Johanna; Romijn, Fred P. H. T. M.; Hack, C. Erik; Sturk, Augueste (Thrombosis and Haemostasis, 2001)
Aim. We investigated the occurrence and thrombin generating mechanisms of circulating microparticles (MP) in patients with multiple organ dysfunction syndrome (MODS) and sepsis.Methods. MP, isolated from blood of patients (n = 9) and healthy controls (n = 14), were stained with cell-specific monoclonal antibodies (MoAbs) or anti-tissue factor (anti-TF) MoAb and annexin V, and analyzed by flow cytometry. To assess their thrombin-generating capacity, MP were reconstituted in normal plasma. The coagulation activation status in vivo was quantified by plasma prothrombin fragment F1+2- and thrombin-antithrombin (TAT) measurements.Results. Annexin V-positive MP in the patients originated predominantly from platelets (PMP), and to a lesser extent from erythrocytes, endothelial cells (EMP) and granulocytes (GMP). Compared to healthy controls, the numbers of annexin V-positive PMP and TF-exposing MP were decreased (p = <0.001 for both), EMP were decreased (E-selectin, p = 0.003) or found equal (CD144, p = 0.063), erythrocyte-derived MP were equal (p = 0.726), and GMP were increased (p = 0.008). GMP numbers correlated with plasma concentrations of elastase (r = 0.70, p = 0.036), but not with C-reactive-protein or interleukin-6 concentrations. Patient samples also contained reduced numbers of annexin V-negative PMP, and increased numbers of erythrocyte-derived MP and GMP (p = 0.005, p = 0.021 and p <0.001, respectively). Patient MP triggered thrombin formation, which was reduced compared to the healthy controls (p = 0.008) and strongly inhibited by an anti-factor XII MoAb (two patients), by anti-factor XI MoAb (eight patients) or by anti-TF MoAb (four patients). Concentrations of F1+2 and TAT were elevated (p = 0.005 and p = 0.001, respectively) and correlated inversely with the number of circulating MP (and r = –0.51, p = 0.013, and r = –0.65, p = 0.001, respectively) and their thrombin generation capacity (F1+2: r = –0.62, p = 0.013).Conclusions. In patients with MODS and sepsis relatively low numbers of MP are present that differ from controls in their cellular origin, numbers and coagulation activation mechanisms.
Keywords: Microparticles; coagulation; factor XI; factor XII; tissue factor; sepsis